Mechanical Characterization of Clonal Mulberry (Morus spp.) Genotypes for Multifarious Industrial Timber Applications - , Pankaj Lushan Dutta; , Kallappan Thangamuthu Parthiban; , Indrani Nath; , Manasee Hazarika Ahmed (Archives of Current Research International, 2025)
Aims: This study aimed to assess the mechanical properties of five mulberry (Morus spp.) clonal genetic resources to identify superior candidates for diverse timber-based industrial applications. Study Design: The investigation employed a Completely Randomized Design (CRD) with replicates, and statistical analyses were performed using ANOVA and Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Place and Duration of Study: Wood samples were collected from a 7-year-old plantation at the Forest College and Research Institute, Mettupalayam, and tests were conducted at the Central Wood Testing Laboratory, Rubber Board, Kottayam during 2023–2024. Methodology: Five mulberry clones were subjected to destructive mechanical testing based on IS 1708 (1986) standards. Tests included modulus of rupture (MOR), modulus of elasticity (MOE), compressive strength (parallel and perpendicular to grain), shear strength, tensile strength, hardness, and nail and screw withdrawal strength. Samples were processed to specified dimensions and tested using a Universal Testing Machine under standardized environmental conditions. Results: Clone ME-0168 exhibited the highest mechanical strength across multiple parameters: MOR (819.85 kgcm-²), MOE (82.89×10³ kgcm-²), compressive strength parallel and perpendicular to grain (420.42 kg cm-²and 152.57 kgcm-²), shear strength (104.10 kgcm-²), and nail and screw holding power (Radial, Tangential, and End- 157.72kg, 149.71kg, 93.71kg and 301.72kg, 329.92kg, 272.22kg respectively). These properties strongly correlate with industrial requirements: high MOR and MOE make it ideal for beams and planks, high compressive and tensile strengths support use in sports gear, and superior nail and screw holding capacity suits furniture and cabinet work. Conclusion: Mulberry, particularly clone ME-0168, demonstrates strong potential for use in timber-based industries such as furniture, cabinet work, and sports equipment. Its favorable mechanical properties and fast growth make it a sustainable alternative in agroforestry and plantation programs addressing India’s rising wood demand.